Random Serum Cortisol as a Predictor for Survival of Terminally Ill Patients With Cancer: A Preliminary Study. (April 2016) - Kim, Hyo Min; Ha, Kyung Sang; Hwang, In Cheol; Ahn, Hong Yup; Youn, Chang Ho
Although previous research found that serum cortisol levels were associated with cancer prognosis, it is unclear whether this association remains robust even at the very end of life of patients with cancer. We conducted a retrospective chart review of 125 patients with terminal cancer to investigate the role of random serum cortisol levels in predicting the remaining life expectancy. The high random cortisol group had a significantly shorter survival time than the low random cortisol group (7.5 vs 26 days). After adjusting for potential confounders, key factors such as poor performance status, hypoalbuminemia, and high random cortisol level are associated with poor survival. Our results suggest that the random serum cortisol level is an independent predictor of survival time of patients with terminally ill cancer.